A chloroquine resistance locus in the rodent malaria parasite Plasmodium chabaudi. - Carlton, J; Mackinnon, M; Walliker, D (1998)
We have located a possible chloroquine resistance locus in the genome of the rodent malaria parasite Plasmodium chabaudi. Two genetically distinct clones of the parasite were grown in vivo and allowed to undergo genetic crossing. The clones differed from each other in their susceptibility to chloroquine; AS(3CQ) had been selected for a low level of resistance to the drug whereas AJ is chloroquine-sensitive. Independent recombinant progeny (20) were cloned from the products of two crosses, phenotyped for their susceptibility to chloroquine, and genotyped for their inheritance of 46 chromosome-specific markers. No association was found between chloroquine susceptibility and the inheritance of pcmdr1, the P. chabaudi homologue of the pfmdr1 multi-drug resistance gene of P. falciparum. Also, there was no association between chloroquine susceptibility and the inheritance of a marker linked to a putative chloroquine resistance locus in a P. falciparum cross. However, 16 of the progeny clones showed co-segregation of four linked markers on chromosome 11 with their resistance phenotype. This result suggests that a locus for chloroquine resistance exists on this chromosome in P. chabaudi.